Karen Armstrong: Remembering Karelia. A Family’s Story of Displacement during and after the Finnish Wars. New York: Berghahn Books 2004. 160 sider. ISBN 1- 57181-650-X hardback. Pris: £40. - Rønne, Kirsten (Tidsskriftet Antropologi, 2005)
Intet resumé